Arsenic antimony soot particles and preparation method thereof
By combining high antimony and low arsenic soot with modified xanthan gum and sodium silicate and using boiling granulator for fluidization granulation and drying, closely combined arsenic and antimony soot particles were prepared, which solved the problems of dust exceeding the standard and waste of valuable metals caused by small particle size and light weight of the soot, and achieved more efficient soot treatment and resource recycling.
Patent Information
- Application Number
- CN202510213534.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-26
AI Technical Summary
The soot with high antimony and arsenic content produced during the ignition smelting process is easy to cause blockage of dust collection pipelines and exceed the standard due to its small particle size and light weight, which affects the production environment and employee health, and also leads to waste of valuable metals.
By combining high antimony and low arsenic soot with modified xanthan gum and sodium silicate and fluidized granulation and drying with boiling granulator, closely bound arsenic and antimony soot particles are prepared to reduce dust flying and particle breakage.
It improves the coagulation, stability and uniformity of soot particles, reduces dust spillage and particle dispersion, and reduces dust load and waste of valuable metals during smelting.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soot disposal, and in particular to arsenic antimony soot particles and a preparation method thereof. Background Art
[0002] In some pyrometallurgical processes, soot containing a certain amount of antimony and arsenic (such as copper blast furnace soot, etc.) is often produced, which has a certain recycling value. However, in actual production, lead soot and slag are fed into the top feed port of the side-blown furnace with the feeding belt. Because the soot itself has a small particle size and light weight, the soot has not yet reached the bottom of the furnace to melt. Most of the soot is sucked into the dust collection pipeline with the negative pressure of the dust collection in the furnace, which is easy to cause pipeline blockage and increase the process dust collection load. At the same time, during the belt batching process, the soot overflows, causing the dust in the workshop to exceed the standard, seriously affecting the production environment of the workshop and the physical and mental health of employees. During the smelting process, a large amount of unburned fine ash escapes with the flue gas. The vicious cycle of soot leads to a large soot rate, resulting in repeated smelting, increased processing costs, and also leads to waste of valuable metals. In order to effectively solve the various disadvantages of soot before and during the furnace, reduce dust during transportation, and reduce dust overflow when entering the furnace. The fly ash needs to be granulated or pelletized to become a solid state before entering the furnace, thereby effectively solving the problem of dust and spillage.
[0003] At present, the granulation of soot mainly adopts drum mixing granulation and twin-screw extrusion granulation. In the drum mixing process, the ratio of soot to water needs to be strictly controlled, otherwise it cannot be pelletized. This is very demanding on the operation, the success rate is not high and the granulation effect is not good. Although twin-screw extrusion granulation can meet the basic requirements of soot granulation, the long-term use cost is very huge. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide an arsenic-antimony soot particle and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] A method for preparing arsenic antimony soot particles comprises the following steps:
[0007] (1) 1000 parts by weight of high-antimony low-arsenic fly ash, 80-100 parts by weight of water, and 0.1-0.2 parts by weight of modified xanthan gum are stirred and mixed to obtain wet high-antimony low-arsenic fly ash;
[0008] (2) 100 parts by weight of water, 1-3 parts by weight of modified xanthan gum, and 1-4 parts by weight of sodium silicate are stirred and mixed to obtain an adhesive solution;
[0009] (3) fluidizing and granulating the wet high-antimony and low-arsenic fly ash through a boiling granulator, and drying the arsenic-antimony fly ash particles, and spraying the binder solution through an atomizer during the fluidization process;
[0010] The modified xanthan gum is prepared by grafting and copolymerizing (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate and (Z)-octadec-9-ene-1-sulfonic acid sodium on xanthan gum.
[0011] The modified xanthan gum is prepared by the following method:
[0012] Under nitrogen protection, deionized water, xanthan gum, and (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate are stirred and mixed, and the temperature is raised to 40-50° C.; at the same time, (Z)-octadec-9-ene-1-sulfonic acid sodium solution and ammonium persulfate solution are slowly added dropwise for 10-30 minutes, and the graft copolymerization reaction is carried out for 2-3 hours to obtain modified xanthan gum.
[0013] The mass ratio of the deionized water, xanthan gum, (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate, (Z)-octadec-9-ene-1-sulfonic acid sodium solution, and ammonium persulfate solution is 200:30:(3-5):(10-20):(5-10).
[0014] The concentration of the ammonium persulfate solution is 0.01-0.05 mol / L.
[0015] The (Z)-octadec-9-ene-1-sulfonic acid sodium solution is an aqueous solution with a concentration of 25-30wt%.
[0016] The specific process parameters of fluidized granulation and drying of the boiling granulator are as follows:
[0017] (1) Turn on the fluidized bed granulator, set the initial granulation temperature to 40-50°C, fluidize the wet high-antimony and low-arsenic fly ash in the fluidized bed granulator through hot air, and set the hot air granulation temperature to 50-75°C;
[0018] (2) Start spraying, the spray speed is 50-70rpm, the atomization pressure is 0.2-0.3MPa, and the spray time is 20-40min;
[0019] (3) After spraying, hot air drying is performed for 20-60 minutes to obtain arsenic antimony ash particles.
[0020] The arsenic antimony soot particles are prepared by the method for preparing the arsenic antimony soot particles.
[0021] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:
[0022] The invention prepares a novel modified xanthan gum by graft copolymerization of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate and (Z)-octadec-9-ene-1-sodium sulfonate on xanthan gum. The modified xanthan gum introduces cationic groups and hydrophobic groups through graft copolymerization, has better adhesion and dispersibility, can effectively enhance the cohesion of particles, makes ash particles more closely combined, reduces dust flying, and improves the stability and uniformity of particles.
[0023] The introduction of sodium (Z)-octadec-9-ene-1-sulfonate gives xanthan gum better surface activity, further enhancing its ability to wrap soot particles. Soot is usually prone to aggregation due to static electricity. By introducing (3-hydroxypropyl) trimethylammonium chloride-2-hydroxycrotonate into the modified xanthan gum, the agglomeration of soot particles caused by electrostatic adsorption during the granulation process can be reduced, and the quality and consistency of the particles can be improved. At the same time, the modified xanthan gum has better thermal stability, which can avoid or reduce the dispersion of arsenic antimony soot particles into powder when entering the top of the side-blown furnace, and prevent the soot from being sucked away by negative pressure.
[0024] By combining modified xanthan gum with sodium silicate as a binder, the bonding force between ash particles can be significantly enhanced, and the strength and stability of the particles can be improved. Sodium silicate can form a strong inorganic network structure to enhance the mechanical strength of the particles; modified xanthan gum further improves the toughness and compressive strength of the particles through its flexibility and bonding properties. This composite binder system can keep the integrity of ash particles during subsequent transportation and handling, reducing dust flying and particle breakage. DETAILED DESCRIPTION
[0025] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.
[0026] Example 1 Preparation of modified xanthan gum:
[0027] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 3g of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate were stirred and mixed, and the temperature was raised to 40°C; at the same time, 10g of (Z)-octadec-9-ene-1-sulfonic acid sodium solution (30wt% aqueous solution) and 5g of ammonium persulfate solution (0.05mol / L) were slowly added dropwise for 10min, and the graft copolymerization reaction was carried out for 3h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0028] Example 2 Preparation of modified xanthan gum:
[0029] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 4g of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate were stirred and mixed, and the temperature was raised to 45°C; at the same time, 15g of (Z)-octadec-9-ene-1-sulfonic acid sodium solution (28wt% aqueous solution) and 8g of ammonium persulfate solution (0.025mol / L) were slowly added dropwise for 20min, and the graft copolymerization reaction was carried out for 2.5h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0030] Example 3 Preparation of modified xanthan gum:
[0031] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 5g of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate were stirred and mixed, and the temperature was raised to 50°C; at the same time, 20g of (Z)-octadec-9-ene-1-sulfonic acid sodium solution (25wt% aqueous solution) and 10g of ammonium persulfate solution (0.01mol / L) were slowly added dropwise for 30min, and the graft copolymerization reaction was carried out for 2h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0032] Example 4 Preparation of Arsenic Antimony Soot Particles:
[0033] (1) 1000 parts by weight of high-antimony low-arsenic fly ash, 80 parts by weight of water, and 0.1 parts by weight of modified xanthan gum (prepared in Example 1) were stirred and mixed to obtain wet high-antimony low-arsenic fly ash;
[0034] (2) 100 parts by weight of water, 1 part by weight of modified xanthan gum (prepared in Example 1), and 1 part by weight of sodium silicate were stirred and mixed to obtain an adhesive solution;
[0035] (3) 5 kg of wet high-antimony and low-arsenic fly ash is subjected to fluidized granulation and drying by a boiling granulator to obtain arsenic-antimony fly ash particles, and the binder solution is sprayed by an atomizer during the fluidization process;
[0036] The specific process parameters of fluidized bed granulation and drying of the boiling granulator are as follows: start the boiling granulator, set the initial granulation temperature to 40°C, fluidize the wet high-antimony and low-arsenic fly ash in the boiling granulator by hot air, and set the hot air granulation temperature to 50°C; start spraying, the spray speed is 50rpm, the atomization pressure is 0.2MPa, and the spray time is 40min; after the spraying is completed, hot air drying is performed for 60min to obtain arsenic antimony fly ash particles.
[0037] Example 5 Preparation of Arsenic Antimony Soot Particles:
[0038] (1) 1000 parts by weight of high-antimony low-arsenic fly ash, 90 parts by weight of water, and 0.15 parts by weight of modified xanthan gum (prepared in Example 2) were stirred and mixed to obtain wet high-antimony low-arsenic fly ash;
[0039] (2) 100 parts by weight of water, 2 parts by weight of modified xanthan gum (prepared in Example 2), and 3 parts by weight of sodium silicate were stirred and mixed to obtain an adhesive solution;
[0040] (3) 5 kg of wet high-antimony and low-arsenic fly ash is subjected to fluidized granulation and drying by a boiling granulator to obtain arsenic-antimony fly ash particles, and the binder solution is sprayed by an atomizer during the fluidization process;
[0041] The specific process parameters of fluidized bed granulation and drying of the boiling granulator are as follows: start the boiling granulator, set the initial granulation temperature to 45°C, fluidize the wet high-antimony and low-arsenic fly ash in the boiling granulator by hot air, and set the hot air granulation temperature to 65°C; start spraying, the spray speed is 60rpm, the atomization pressure is 0.25MPa, and the spray time is 30min; after the spraying is completed, hot air drying is performed for 45min to obtain arsenic antimony fly ash particles.
[0042] Example 6 Preparation of Arsenic Antimony Soot Particles:
[0043] (1) 1000 parts by weight of high-antimony low-arsenic fly ash, 100 parts by weight of water, and 0.2 parts by weight of modified xanthan gum (prepared in Example 3) were stirred and mixed to obtain wet high-antimony low-arsenic fly ash;
[0044] (2) 100 parts by weight of water, 3 parts by weight of modified xanthan gum (prepared in Example 3), and 4 parts by weight of sodium silicate were stirred and mixed to obtain an adhesive solution;
[0045] (3) 5 kg of wet high-antimony and low-arsenic fly ash is subjected to fluidized granulation and drying by a boiling granulator to obtain arsenic-antimony fly ash particles, and the binder solution is sprayed by an atomizer during the fluidization process;
[0046] The specific process parameters of fluidized bed granulation and drying of the boiling granulator are as follows: start the boiling granulator, set the initial granulation temperature to 50°C, fluidize the wet high-antimony and low-arsenic fly ash in the boiling granulator by hot air, and set the hot air granulation temperature to 75°C; start spraying, the spray speed is 70rpm, the atomization pressure is 0.3MPa, and the spray time is 20min; after the spraying is completed, hot air drying is performed for 20min to obtain arsenic antimony fly ash particles.
[0047] Comparative Example 1
[0048] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that no modified xanthan gum is added to the binder solution sprayed by the atomizer.
[0049] Comparative Example 2
[0050] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum is replaced by xanthan gum in the binder solution sprayed by the atomizer.
[0051] Comparative Example 3
[0052] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that no sodium silicate is added to the binder solution sprayed by the atomizer.
[0053] Comparative Example 4
[0054] The preparation method of the arsenic-antimony fly ash particles in this comparative example is basically the same as that in Example 5, except that no modified xanthan gum is added during the preparation of the wet high-antimony and low-arsenic fly ash in step (1).
[0055] Comparative Example 5
[0056] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum in the binder solution sprayed by the atomizer is replaced with xanthan gum prepared by the following method;
[0057] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 4g of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate were stirred and mixed, and the temperature was raised to 45°C; 8g of ammonium persulfate solution (0.025mol / L) was slowly added dropwise for 20min, and the graft copolymerization reaction was carried out for 2.5h. After cooling to room temperature, 400g of acetone was added, stirred, precipitated, and filtered to obtain modified xanthan gum.
[0058] Comparative Example 6
[0059] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum in the binder solution sprayed by the atomizer is replaced with xanthan gum prepared by the following method;
[0060] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 4g of methacryloyloxyethyltrimethylammonium chloride were stirred and mixed, and the temperature was raised to 45°C; at the same time, 15g of (Z)-octadec-9-ene-1-sulfonic acid sodium solution (28wt% aqueous solution) and 8g of ammonium persulfate solution (0.025mol / L) were slowly added dropwise for 20min, and the graft copolymerization reaction was carried out for 2.5h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0061] Comparative Example 7
[0062] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum in the binder solution sprayed by the atomizer is replaced with xanthan gum prepared by the following method;
[0063] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 4g of (3-acrylamidopropyl)trimethylammonium chloride were stirred and mixed, and the temperature was raised to 45°C; at the same time, 15g of (Z)-octadec-9-ene-1-sulfonic acid sodium solution (28wt% aqueous solution) and 8g of ammonium persulfate solution (0.025mol / L) were slowly added dropwise for 20min, and the graft copolymerization reaction was carried out for 2.5h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0064] Comparative Example 8
[0065] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum in the binder solution sprayed by the atomizer is replaced with xanthan gum prepared by the following method;
[0066] Under nitrogen protection, 200g of deionized water, 30g of xanthan gum, and 4g of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate were stirred and mixed, and the temperature was raised to 45°C; at the same time, 15g of sodium tetradecene-1-sulfonate solution (28wt% aqueous solution) and 8g of ammonium persulfate solution (0.025mol / L) were slowly added dropwise for 20min, and the graft copolymerization reaction was carried out for 2.5h. After cooling to room temperature, 400g of acetone was added, stirred and precipitated, and filtered to obtain modified xanthan gum.
[0067] Comparative Example 9
[0068] The preparation method of the arsenic antimony soot particles in this comparative example is basically the same as that in Example 5, except that the modified xanthan gum in the binder solution sprayed by the atomizer is replaced with xanthan gum prepared by the following method;
[0069] Under nitrogen protection, add 300g of deionized water and 100g of xanthan gum to the reaction bottle, stir to mix, and heat to 45°C; slowly add 30g of methyl methacrylate ethanol solution (28wt%), 40g of methacryloyloxyethyltrimethylammonium chloride solution (75wt%), and 2.8g of ammonium persulfate solution (0.08mol / L) to the reaction bottle at the same time, add for 1h, graft copolymerize for 1.5h, cool to room temperature, add 600g of acetone, stir to precipitate, and filter to obtain modified xanthan gum.
[0070] The xanthan gum used in the examples and comparative examples of the present application is FT11 type industrial grade xanthan gum purchased from Shandong Fengtai Biotechnology Co., Ltd.; the modulus of sodium silicate is 2.5. The main components of the high antimony and low arsenic soot used in the examples and comparative examples of the present application are: 2.8wt% lead oxide, 1.1wt% bismuth oxide, 69.3wt% antimony oxide, 25.5wt% arsenic oxide, and 80wt% of the soot particle size is between 1-3μm.
[0071] The boiling granulator used in this application is produced by Changzhou Ruili Drying Equipment Co., Ltd., model FL-5. The working principle of the boiling granulator is: the powdered material for granulation is put into the fluidized bed, and the cold air enters the rear heating chamber through the primary and medium efficiency filters. After being heated to the required temperature for the inlet air by the heater, it enters the fluidized bed. Under the pull of the induced draft fan, the material is fluidized in the bed. The granulation adhesive is sent into the atomizer by the infusion pump, sprayed onto the fluidized material after atomization, and the water is taken out of the machine by the fan after evaporation.
[0072] The particle size and wear rate of the arsenic antimony soot particles prepared in Examples 4-6 and Comparative Examples 1-9 were tested. The test results are shown in Table 1.
[0073] Particle size test: The particle size distribution is measured by sieve classification. The mesh sizes used in this application are 10, 15, 20, 25, 30, 35, 40, 45, and 50 mesh. The test data is illustrated as follows: D10=25 mesh means that the weight of particles sieved through a 25-mesh sieve is 10% (or just over 10%), and the weight of particles sieved through a 30-mesh sieve is less than 10%.
[0074] The wear rate test was conducted by blowing and grinding: 40g of arsenic antimony soot particles were placed in a straight tube (inner diameter 25mm, length 440mm, nozzle inner diameter 1mm), and the sample was blown and ground for 30 minutes under a constant airflow (12.0±0.1L / min) to simulate the wear process. During the experiment, the particle sample collided and rubbed with the tube wall or other sample particles under the action of high-speed airflow, generating fine powder.
[0075] Wear rate = fine powder weight / initial particle weight × 100%.
[0076] Table 1
[0077]
[0078] It can be seen from the data of Examples 4, 5 and 6 in Table 1 that the particle size of the arsenic antimony soot particles prepared in the present application is mainly between 15 and 25 meshes, and the wear rate is relatively low.
[0079] Comparative Example 1 is a comparative example without adding modified xanthan gum. It can be seen from the data in Table 1 that the particle size is small and the wear rate reaches 39.8%.
[0080] Comparative Examples 2, 5, 6, 7, 8 and 9 are comparative examples without adding modified xanthan gum and adding xanthan gum modified in other ways. It can be seen from Table 1 that the wear rate of the prepared arsenic antimony soot particles is relatively high.
[0081] Comparative Example 3 is a comparative example in which no sodium silicate is added to the adhesive solution. It can be seen from Table 1 that its wear rate reaches 41.4%.
[0082] Comparative Example 4 is a comparative example in which modified xanthan gum is not added during the preparation of wet high antimony and low arsenic ash. It can be seen from Table 1 that its wear rate is higher than that of Examples 4-6 of the present application. Since the particle size of high antimony and low arsenic ash is uniformly distributed between 1-3 μm and the particles are relatively small, if it is directly added to a boiling granulator for fluidization and spray granulation, the fluidization state is difficult to control, and it is easy to cause the bag on the bag filter of the boiling granulator to adsorb more ash, and the bag filter shakes the cylinder load, making it difficult to perform granulation operations. In the preparation of wet high antimony and low arsenic ash, the present application adds a small amount of modified xanthan gum, so that the prepared wet high antimony and low arsenic ash can form a good fluidization state in the boiling granulator, which is easy to fluidize and granulate.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing arsenic antimony soot particles, characterized in that: The following steps are involved: (1) 1000 parts by weight of high-antimony low-arsenic fly ash, 80-100 parts by weight of water, and 0.1-0.2 parts by weight of modified xanthan gum are stirred and mixed to obtain wet high-antimony low-arsenic fly ash; (2) 100 parts by weight of water, 1-3 parts by weight of modified xanthan gum, and 1-4 parts by weight of sodium silicate are stirred and mixed to obtain an adhesive solution; (3) fluidizing and granulating the wet high-antimony and low-arsenic fly ash through a boiling granulator, and drying the arsenic-antimony fly ash particles, and spraying the binder solution through an atomizer during the fluidization process; The modified xanthan gum is prepared by grafting and copolymerizing (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate and (Z)-octadec-9-ene-1-sulfonic acid sodium on xanthan gum.
2. The method for preparing arsenic antimony soot particles according to claim 1, characterized in that: The modified xanthan gum is prepared by the following method: Under nitrogen protection, deionized water, xanthan gum, and (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate are stirred and mixed, and the temperature is raised to 40-50° C.; at the same time, (Z)-octadec-9-ene-1-sulfonic acid sodium solution and ammonium persulfate solution are slowly added dropwise for 10-30 minutes, and the graft copolymerization reaction is carried out for 2-3 hours to obtain modified xanthan gum.
3. The method for preparing arsenic antimony soot particles according to claim 2, characterized in that: The mass ratio of the deionized water, xanthan gum, (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate, (Z)-octadec-9-ene-1-sulfonic acid sodium solution, and ammonium persulfate solution is 200:30:(3-5):(10-20):(5-10).
4. The method for preparing arsenic antimony soot particles according to claim 2, characterized in that: The concentration of the ammonium persulfate solution is 0.01-0.05 mol / L.
5. The method for preparing arsenic antimony soot particles according to claim 2, characterized in that: The (Z)-octadec-9-ene-1-sulfonic acid sodium solution is an aqueous solution with a concentration of 25-30wt%.
6. The method for preparing arsenic antimony soot particles according to claim 1, characterized in that: The specific process parameters of fluidized granulation and drying of the boiling granulator are as follows: (1) Turn on the fluidized bed granulator, set the initial granulation temperature to 40-50°C, fluidize the wet high-antimony and low-arsenic fly ash in the fluidized bed granulator through hot air, and set the hot air granulation temperature to 50-75°C; (2) Start spraying, the spray speed is 50-70rpm, the atomization pressure is 0.2-0.3MPa, and the spray time is 20-40min; (3) After spraying, hot air drying is performed for 20-60 minutes to obtain arsenic antimony ash particles.
7. Arsenic antimony soot particles prepared by the method for preparing arsenic antimony soot particles according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of efficient smoke agglomeration agent
CN113637456A
Rapid dispersive and dissoluble granula of biopolymer
CN87104169A